Potential of Bioactive Compounds from Gambier (Uncaria Gambir Roxb.) in Modulating Cognitive Function: A Scoping Review - Rahmi Novita Yusuf; Adrial Adrial; Desmawati Desmawati; Nur Indrawaty Lipoeto (Indonesian Journal of Global Health Research, 2025)
Aging is a process of diminishing tissue capacity for self-repair and maintenance of normal structure and function, leading to vulnerability to injury and damage. The high incidence of neurodegenerative diseases coincides with increased life expectancy in the elderly. An unavoidable negative effect of neurodegenerative diseases is the potential to cause cognitive decline. Gambier (Uncaria gambir Roxb.), containing 90% catechin, is a traditional plant with potential to enhance cognitive function. This scoping review aims to map existing research on the potential of bioactive compounds from gambier in modulating cognitive function, based on research articles in journals from the last 10 years in the PubMed, PMC, Google Scholar, and Google Scholar databases (2014-2024). The research was conducted by collecting research data from the last 10 years, totaling 12 articles. Among these, 4 articles met the inclusion criteria, focusing on the potential of bioactive compounds from gambier in modulating cognitive function. The article screening was conducted systematically using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) as 1 a guideline, followed by screening based on inclusion and exclusion criteria. This scoping review found potential for bioactive compounds from gambier in modulating cognitive function, as evidenced by increased Montreal Cognitive Assessment (MoCA) scores, decreased levels of Beta Amyloid (Aβ), Microtubule-Associated Protein Tau (MAPT), Malondialdehyde (MDA) levels, and increased Brain-Derived Neurotrophic Factor (BDNF). The potential of catechin, the primary bioactive compound in gambier, which possesses antioxidant, anti-inflammatory, and neuroprotective effects, yields beneficial results in enhancing cognitive function in the elderly.